Sex Differences in the Association Between Measures of General and Central Adiposity and the Risk of Myocardial Infarction: Results From the UK Biobank - Peters, Sanne A. E. (J Am Heart Assoc, 2018)
BACKGROUND: There are substantial differences in the distribution of adipose tissue between women and men. We assessed the sex‐specific relationships and their differences between measures of general and central adiposity and the risk of incident myocardial infarction (MI). METHODS AND RESULTS: Between 2006 and 2010, the UK Biobank recruited over 500 000 participants aged 40 to 69 years across the United Kingdom. During 7 years of follow‐up, 5710 cases of MI (28% women) were recorded among 265 988 women and 213 622 men without a history of cardiovascular disease at baseline. Cox regression models yielded adjusted hazard ratios for MI associated with body mass index, waist circumference, waist‐to‐hip ratio, and waist‐to‐height ratio. There was an approximate log‐linear relationship between measures of general and central adiposity and the risk of MI in both sexes. A 1‐SD higher in body mass index, waist circumference, waist‐to‐hip ratio, and waist‐to‐height ratio, respectively, were associated with hazard ratios (confidence intervals) for MI of 1.22 (1.17; 1.28), 1.35 (1.28; 1.42), 1.49 (1.39; 1.59), and 1.34 (1.27; 1.40) in women and of 1.28 (1.23; 1.32), 1.28 (1.23; 1.33), 1.36 (1.30; 1.43), and 1.33 (1.28; 1.38) in men. The corresponding women‐to‐men ratios of hazard ratios were 0.96 (0.91; 1.02), 1.07 (1.00; 1.14), 1.15 (1.06; 1.24), and 1.03 (0.97; 1.09). CONCLUSIONS: Although general and central adiposity measures each have profound deleterious effects on the risk of MI in both sexes, a higher waist circumference and waist‐to‐hip ratio conferred a greater excess risk of MI in women than in men. Waist‐to‐hip ratio was more strongly associated with the risk of MI than body mass index in both sexes, especially in women.